The The Effect of Organizational Culture, Transformational Leadership, and Job Satisfaction of the National Library Republic of Indonesia on Organizational Citizenship Behavior (OCB): 1Ikawati Lestari, 2Setyo Riyanto 1Master of Management Student, Mercu Buana University, Jakarta, Indonesia 2Associate Professor at Mercu Buana University, Jakarta, Indonesia ikawatilestari@gmail.com; setyo.riyanto@mercubuana.ac.id - Lestari, Ikawati (Archives of Business Research, 2021)
ABSTRACT The library is the builder of all libraries in Indonesia (Law No.43 of the Republic of Indonesia Year 2007). As a coach, the National Library of Indonesia faces challenges that must be met so that organizational performance needs to be improved. If every employee has organizational citizenship behavior (OCB), can achieve good government. The end of this study is to realize the effects of corporate culture, transformational leadership, and job satisfaction on organizational citizenship behavior (OCB) of the National Library of Indonesia. The resource persons in this study involved 280 ASN informants who had served at the National Library for at least three years—used linear regression method to analyze the data and SPSS version 17.0 for data analysis. The results of the analysis of this study instruct organizational culture, transformational leadership, and organizational citizenship behavior (OCB). Keywords: Organizational Culture, Transformational Leadership, Job Satisfaction, Organizational Citizenship Behavior (OCB)